Humor Practises Of Arabic Teachers And Speaking Anxiety - Baharudin, Harun; Wan Anuar, Wan Muhammad Radzi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The use of humor by teachers in classroom interactions can stimulate students and change their attitudes toward learning. The study aims to determine the level of humor applied among Arabic teachers (GBA) and students' speaking anxiety in the Arabic language class at the Government Aided Religious Secondary School (SABK) in Kerian, Perak, Malaysia. A total of 152 out of 258 fourth-form students were selected as a sample by stratified random sampling technique. The research instrument was a questionnaire that was adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) (Horwitz et al., 1986) and the Students' Evaluation of Teaching Effectiveness Rating Scale (SETERS) (Toland & Ayala, 2005). The study found that the frequency of GBA humor practice was moderately low (M = 2.88, SP = 0.50). At the same time, the frequency of students' speaking anxiety in Arabic is relatively high (M = 3.12, SP = 0.74). Pearson's correlation test shows a significant relationship with weak negative strength (r = -.197, p =.000) between the frequency of GBA humor practice and the level of students' speaking anxiety in Arabic. In conclusion, although the frequency of GBA humor practices is medium-low, most GBA use cheerful humor practices compared to hostile ones. However, the method of GBA humor alone is not enough to reduce the frequency of students' speaking anxiety in Arabic. Therefore, every party, especially teachers, must significantly diversify other effective teaching practices in teaching Arabic to improve students' speaking skills.